markl77
New member
- Joined
- Feb 5, 2017
- Messages
- 33
Hello,
this is the question I was given. For a geometric sequence, term 4 = 4x+8 and term 7 = x-4. If the common ratio is (1/2), what is the first term?
My initial work to do this question was t multiply (1/2) by term 4, which equals (2x+4), but if I go on with that common ratio it does not ever give me (x-4). I decided that I would have to figure out what x was before I could use the common ratio that was given.
To find x I looked at how term 7 - term 4 = 3, so therefore (1/2) * 3 would equal the amount I would have to multiply (4x+8) to get to (x-4).
1.5(4x+8)=(x-4)
6x+12=x-4
x=-3.2
So then I used -3.2 as x in the term (4x+8) going to the right to see if it would eventually equal (-7.2)
(4)(-3.2)+8=-4.8
-4.8*(1/2)=-2.4
And from there it just got smaller. I'm just wondering what I'm doing incorrectly in solving for x, and why in this case using (1/2) multiplied by the term (4x+8) doesn't eventually equal to (x-4)
Help is appreciated!
this is the question I was given. For a geometric sequence, term 4 = 4x+8 and term 7 = x-4. If the common ratio is (1/2), what is the first term?
My initial work to do this question was t multiply (1/2) by term 4, which equals (2x+4), but if I go on with that common ratio it does not ever give me (x-4). I decided that I would have to figure out what x was before I could use the common ratio that was given.
To find x I looked at how term 7 - term 4 = 3, so therefore (1/2) * 3 would equal the amount I would have to multiply (4x+8) to get to (x-4).
1.5(4x+8)=(x-4)
6x+12=x-4
x=-3.2
So then I used -3.2 as x in the term (4x+8) going to the right to see if it would eventually equal (-7.2)
(4)(-3.2)+8=-4.8
-4.8*(1/2)=-2.4
And from there it just got smaller. I'm just wondering what I'm doing incorrectly in solving for x, and why in this case using (1/2) multiplied by the term (4x+8) doesn't eventually equal to (x-4)
Help is appreciated!